Analisis Community Based Tourism dalam Pengembangan Wisata Pulau Gili Iyang di Kecamatan Dungkek Kabupaten Sumenep - Rony Wirawan; Sasmito Jati Utama; Deasy Arieffiani (Faculty of Social and Political Science, 2023)
Tourism management is an effort to develop tourism villages that have valuable natural potential. This research concerns the development of tourism in Banraas Village, Gili Island, which is based on Community Based Tourism. This management is expected to have a positive impact on Pokdarwis and the people of Banraas Village who contribute directly to its development. Researchers are interested in taking the location of Giliyang Island which is known to have the 2nd highest oxygen levels in the world, especially in Banraas Village. This research aims to describe and analyze community-based tourism development Community Based Tourism in Banraas Village, Giliyang Island, Dungkek District, Sumenep Regency. At the same time describing and analyzing the inhibiting or supporting factors for community-based tourism development Community Based Tourism in Banraas Village, Giliyang Island, Dungkek District, Sumenep Regency. This research method is qualitative which refers to the Community Based Tourism theory approach Suansri (2003), namely the approach of economic principles, social principles, cultural principles, environmental principles and political principles. Data collection techniques from this study are the results of interviews with informants, observation, and documentation. The results of this study are that tourism management in Banraas Village applies a Community Based Tourism approach that refers to the Suansri theory, namely the economic principle as evidenced by the role of Pokdarwis in tourism management in Banraas Village by empowering local communities. On social principles, Banraas Village tourism is crowded with visitors supported by facilities. The principle of culture, a society that still adheres to social and religious norms. The principle of the environment, there is the use of trash cans. Political principle, society as a whole is not involved in planning and decision-making processes.